The trend in the relationship of advanced maternal age to preterm birth and low birthweight - Sohn, Kitae (Informa Healthcare, 2017)
© 2017 The European Society of Contraception and Reproductive Health. Purpose: As women in developed countries tend to delay childbearing, it becomes more important to understand the relationship of advanced maternal age to birth outcomes. We aimed to estimate the trend in the relationship of advanced maternal age to preterm birth and low birthweight. Materials and methods: We analysed 4,264,417 ethnically homogeneous, singleton firstborns, born in hospitals to married couples in South Korea in 1997–2014. We regressed an indicator for preterm birth or low birthweight on advanced maternal age, the baby’s sex, advanced paternal age, and a set of socioeconomic status (SES) variables by year. We then collected the coefficient on advanced maternal age and charted its trend. We repeated the same procedure for 4,153,313 second- and third births. Results: When we controlled for only the baby’s sex, the relationship between advanced maternal age and preterm birth dramatically weakened in the 2000s and slightly more thereafter: being an older mother was related to a 3.5% point increase in preterm birth in the late 1990s, but this figure decreased to less than 2% points by the early 2010s. Controlling for advanced paternal age slightly decreased the relationship and controlling for SES hardly affected the relationship. We obtained almost the same results for low birthweight. Second- and third-borns exhibited a declining, much weaker influence of advanced maternal age on the birth outcomes. Conclusions: In relative terms, mothers of advanced age were more likely to deliver preterm and low birthweight babies than younger mothers. In absolute terms, however, the risk was small in the 1990s and much smaller in the early 2010s.